2022
DOI: 10.1155/2022/2794243
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Catalpol on Alzheimer’s Disease and Its Mechanisms

Abstract: Alzheimer’s disease (AD) is a degenerative disease of the central nervous system characterized by memory loss and cognitive dysfunction. With the increasing aging of the population, the incidence of AD and the number of patients are also increasing year by year, causing more and more heavy burdens to the family and society. Catalpol, an iridoid glycoside compound, is one of the main active components of Rehmannia glutinosa. At present, a large number of experimental studies in vivo and in vitro have confirmed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 68 publications
(134 reference statements)
0
6
0
Order By: Relevance
“…A series of studies have already demonstrated the immunopotentiating and modulating effects of catalpol against Rehmannia glutinosa (Gaertn.) Steud [ [49] , [50] , [51] ], α-pinene against Angelica gigas Nakai [ [52] , [53] , [54] , [55] ] and loganin and moroniside for Cornus officinalis Siebold & Zucc [ 56 , 57 ].…”
Section: Discussionmentioning
confidence: 99%
“…A series of studies have already demonstrated the immunopotentiating and modulating effects of catalpol against Rehmannia glutinosa (Gaertn.) Steud [ [49] , [50] , [51] ], α-pinene against Angelica gigas Nakai [ [52] , [53] , [54] , [55] ] and loganin and moroniside for Cornus officinalis Siebold & Zucc [ 56 , 57 ].…”
Section: Discussionmentioning
confidence: 99%
“…It has wide pharmacological activities on the blood, immune, endocrine, cardiovascular, and nervous systems [31]. Catalpol, an iridoid glycoside compound in Rehmannia root, has antioxidant, antiinflammatory, antiapoptotic, and neuroprotective effects [32].…”
Section: Pharmaceutical Information Of Nytmentioning
confidence: 99%
“… 8 Recent studies have proven that it has multiple pharmacological effects such as antioxidant, anti-inflammatory, anti-tumor, neuroprotective, hypoglycemic, etc. 9 , 10 In recent years, many studies have focused on the mechanism of catalpol’s hypoglycemic and anti-tumor actions in vivo and in vitro. 9 , 11 , 12 However, the intervention’s effect on dermal fibroblasts’ function is still unclear.…”
Section: Introductionmentioning
confidence: 99%